High-value crops’ embedded groundnut-based production systems vis-à-vis system-mode integrated nutrient management: long-term impacts on system productivity, system profitability, and soil bio-fertility indicators in semi-arid climate - Bana, Ram Swaroop; Choudhary, Anil K.; Nirmal, Ravi C.; Kuri, Bhola Ram; Sangwan, Seema; Godara, Samarth; Bansal, Ruchi; Singh, Deepak; Rana, D.S. (Frontiers in Plant Science, 2024)
The current study identified two new climate-resilient groundnut-based cropping systems (GBCSs), viz., groundnut–fenugreek cropping system (GFCS) and groundnut–marigold cropping system (GMCS), with appropriate system-mode bio-compost embedded nutrient management schedules (SBINMSs) for semi-arid South Asia. This 5-year field study revealed that the GMCS along with leaf compost (LC) + 50% recommended dose of fertilizers (RDF50) in wet-season crop (groundnut) and 100% RDF (RDF100) in winter-season crop (marigold) exhibited the highest system productivity (5.13–5.99 t/ha), system profits (US 1,767–2,688/ha), and soil fertility (available NPK). Among SBINMSs, the application of 5 t/ha leaf and cow dung mixture compost (LCMC) with RDF50 showed the highest increase (0.41%) in soil organic carbon (SOC) followed by LC at 5 t/ha with RDF50 and RDF100. Legume–legume rotation (GFCS) had significantly higher soil microbial biomass carbon (SMBC) and soil microbial biomass nitrogen (SMBN) than legume–non-legume rotations (groundnut–wheat cropping system (GWCS) and GMCS). Among SBINMSs, the highest SMBC (201 µg/g dry soil) and SMBN (27.9 µg/g dry soil) were obtained when LCMC+RDF50 was applied to groundnut. The SMBC : SMBN ratio was the highest in the GWCS. LC+RDF50 exhibited the highest SMBC : SOC ratio (51.6). The largest increase in soil enzymatic activities was observed under LCMC+RDF50. Overall, the GMCS with LC+RDF50 in the wet season and RDF100 in the winter season proved highly productive and remunerative with better soil bio-fertility. SBINMSs saved chemical fertilizers by 25%’ in addition to enhanced system productivity and system profits across GBCSs in semi-arid regions of South Asia. Future research needs to focus on studying the potential of diversified production systems on water and environmental footprints, carbon dynamics, and energy productivity under semi-arid ecologies.